A double-tuned 1H/23Na dual resonator system for tissue sodium concentration measurements in the rat brain via Na-MRI - Wetterling, Friedrich; Tabbert, Martin; Junge, Sven; Gallagher, Lindsay; Macrae, I. Mhairi; Fagan, Andrew J. (Physics in medicine and biology, 2010)
A method for quantifying the tissue sodium concentration (TSC) in the rat brain from 23Na-MR images was developed. TSC is known to change in a variety of common human diseases and holds considerable potential to contribute to their study; however, its accurate measurement in small laboratory animals has been hindered by the extremely low signal to noise ratio (SNR) in 23Na images. To address this, the design, construction and characterization of a double-tuned 1H/23Na dual resonator system for 1H-guided quantitative 23Na-MRI are described. This system comprises an SNR-optimized surface detector coil for 23Na image acquisition, and a volume resonator producing a highly homogeneous B1 field (<5% inhomogeneity) for the Na channel across the rat head. The resonators incorporated channel-independent balanced matching and tuning capabilities with active decoupling circuitry at the 23Na resonance frequency. A quantification accuracy of TSC of <10 mM was achieved in Na-images with 1.2 µl voxel resolution acquired in 10 min. The potential of the quantification technique was demonstrated in an in vivo experiment of a rat model of cerebral stroke, where the evolution of the TSC was successfully monitored for 8 h after the stroke was induced.
Die 1 und die 23 im Titel sind hochgestellt
Gesehen am 29.11.2023